Growth characteristics of freeze-tolerant baker’s yeast Saccharomyces cerevisiae AFY in aerobic batch culture - Ji, Meng (Springerplus, 2016)
Saccharomyces cerevisiae AFY is a novel baker’s yeast strain with strong freeze-tolerance, and can be used for frozen-dough processing. The present study armed to clarify the growth characteristics of the yeast AFY. Aerobic batch culture experiments of yeast AFY were carried out using media with various initial glucose concentrations, and the culture process was analyzed kinetically. The growth of the yeast AFY exhibited a diauxic pattern with the first growth stage consuming glucose and the second growth stage consuming ethanol. The cell yield decreased with increasing initial glucose concentration in the first growth stage, and also decreased with increasing initial ethanol concentration in the second growth stage. In the initial glucose concentration range of 5.0–40.0 g/L, the simultaneous equations of Monod equation, Luedeking–Piret equation and pseudo-Luedeking–Piret equation could be used to describe the concentrations of cell, ethanol and glucose in either of the two exponential growth phases. At the initial glucose concentrations of 5.0, 10.0 and 40.0 g/L, the first exponential growth phase had a maximal specific cell growth rate of 0.52, 0.98 and 0.99 h(−1), while the second exponential growth phase had a maximal specific cell growth rate of 0.11, 0.06 and 0.07 h(−1), respectively. It was indicated that the efficiency of the yeast production could be improved by reducing the ethanol production in the first growth stage.